A STUDY OF GRIEVANCE HANDLING AND ITS IMPACT ON CONSUMER PERCEPTION: THE CASE OF UBER & OLA (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The goal of any service provider is to satisfy  the customer expectations in order to create  a brand loyalty. However, no service provider  can escape from the service errors as humans  are involved in service delivery. Since the  production and consumption of services  usually occurs concurrently, the quality of a  service is dependent upon the deliverability of  the service provider and the recipient’s utility.  Thus, in order to overcome the limitation of  inevitable errors, service providers must be  concerned with service recovery. As attracting  new customers is costly as compared to  retaining existing customers, it becomes  another important reason for service providers  to must try hard for efficient service recovery.  This empirical investigation is designed to test  effective recovery processes for service failures in  e-hailing by studying the relationship between  compensation, apology, and response time on  perceived justice, service recovery satisfaction,  and repurchase intention of the customer. Our  sample consist 160 students from University of  Delhi, India, who are active e-hailing service  users. The findings indicate that all three  e-hailing service recovery attributes appear to  be key in creating satisfied customers based on  their effects on perceived justice.
Keywords: production; utility; studying